Cytotoxic evaluation of a mixture of four commonly used pesticides on mammalian cell lines - Prudence Agnandji; Eugène S. Attakpa; Fabrice Cazier (Academia Environmental Sciences and Sustainability)
During the last decades, vegetable farming has increased in African cities along with an increasing use of pesticides by the vegetable farmers. This bears the risk of heightened exposure to insecticide residues in the populations consuming these vegetables. In this study, we investigated how four frequently used insecticides, namely cypermethrin (Cyp), cyfluthrin (Cyf), β-hexachlorocyclohexane (β-HCH), and β-endosulfan (β-End), that were previously detected in the blood of vegetable farmers in South Benin act together in mixtures. The cytotoxicity of the four insecticides and their mixture in the same concentration ratio as they had been detected in the blood (27% Cyp, 31% Cyf, 15% β-HCH, and 27% β-End) was tested on the arylhydrocarbon receptor-chemically activated luciferase expression (AhR-CALUX) assay using H4L7.5c2 cells derived from H4IIe. Apart from Cyf, none of the test compounds activated the AhR, but they exhibited cytotoxicity. The inhibitory concentrations for 10% of the cells, IC10, of the individual components were (1.1 ± 0.2) × 10−5 for β-End, (2.2 ± 0.2) × 10−5 M for Cyp, (2.0× ± 0.5) × 10−5 M for Cyf, and (3.8 ± 0.6) × 10−5 M for the mixture. β-HCH was too volatile to cause an effect. The cytotoxicity was compared to a quantitative structure-activity relationship for baseline toxicity, and chemicals were confirmed as baseline toxicants in this cell line. The study showed the need to account for mixture effects when assessing the risk of co-exposure to insecticides.